A chemical polishing liquid for ferrite products and its preparation method and application
By using a chemical polishing liquid containing sulfuric acid, phytic acid, potassium dichromate, polyether modified polysiloxane quaternary ammonium salt and sodium chloride, the ferrite core product is polished, and the problems of low polishing efficiency and high processing cost in the prior art are solved, and a high efficiency and low-cost polishing effect is achieved.
Patent Information
- Application Number
- CN202411546947.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In the prior art, when using chemical polishing liquid to polish ferrite core products, the polishing efficiency is not high, and the concentration of chromium compounds and strong acids is often required to be increased and the treatment time is extended, resulting in high processing costs and damage to the surface structure and performance stability of the workpiece.
Using a chemical polishing liquid containing sulfuric acid, phytic acid, potassium dichromate, polyether modified polysiloxane quaternary ammonium salt and sodium chloride, the wetting and adsorption properties of polyether modified polysiloxane quaternary ammonium salt is significantly improved through the chelation of phytic acid and potassium dichromate, combined with the wetting and adsorption characteristics of the polyether modified polysiloxane quaternary ammonium salt, which significantly improves the polishing efficiency and quality.
It significantly improves the polishing efficiency and quality of ferrite products, reduces the amount of potassium dichromate and sulfuric acid, reduces the treatment cost, and avoids the problem of damage to the surface structure and performance stability of the workpiece.
Smart Images

Figure CN119410273B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferrite core processing aids, and in particular relates to a chemical polishing liquid for ferrite products and a preparation method and application thereof. Background Art
[0002] Some ferrite cores used in electronic components such as inductors have burrs on the edges of their appearance due to their small size and large quantity, which affects the use experience of customers. At present, employees generally use physical polishing to remove burrs. The deburring effect is achieved by rolling and rubbing the polishing materials together. However, the physical polishing process is prone to product damage and cracks, which affects the product yield.
[0003] Polishing with chemical polishing liquid is an alternative to physical polishing, but the current chemical polishing liquid is mainly used for electrochemical polishing and pickling chemical polishing of metal surfaces such as stainless steel. The principle of electrochemical polishing is mainly that the burrs on the workpiece and the active ingredient film in the polishing liquid are adsorbed on the surface of the workpiece. This mucous film is thinner at the protrusions and thicker at the concave parts. Because the current density at the protrusions is high, it dissolves quickly. As the mucous film flows, the concave and convex parts change continuously, and the rough surface is gradually leveled. However, for ferrite core products, they do not have conductive properties. During the electrochemical polishing process, the current density at the concave and convex parts is not much different, and the mucous film at the burr protrusions is thinner and has fewer active ingredients, resulting in low polishing efficiency. Pickling chemical polishing mainly uses chromium pickling liquid to oxidize and passivate the burrs on the workpiece, remove impurities and uneven parts on the workpiece surface, thereby improving the surface finish and corrosion resistance. However, due to the rough hydrophobic effect of the burrs on the workpiece and the large surface tension of the chromium pickling liquid, the wetting adsorption and film-forming effect of the chromium pickling on the burr part is poor, which also leads to low polishing efficiency. In order to improve the polishing efficiency, it is often necessary to increase the concentration of chromium compounds and strong acids, and extend the time of chemical polishing. However, the above operations will greatly increase the processing cost, increase the generation of chromium-containing waste acid, and there will be excessive acid etching reactions, which will lead to the destruction of the surface structure and performance stability of the workpiece matrix. Summary of the invention
[0004] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a chemical polishing liquid for ferrite products.
[0005] Another object of the present invention is to provide a method for preparing the chemical polishing solution.
[0006] Another object of the present invention is to provide application of the above chemical polishing liquid in chemical polishing of ferrite products.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0009] Sulfuric acid 4%-8%, phytic acid 2%-5%, potassium dichromate 1%-6%, polyether modified polysiloxane quaternary ammonium salt 0.5%-5%, sodium chloride 0.2%-2%, and the rest is water.
[0010] The phytic acid used in the present invention has a molecular structure as shown in Formula 1 below:
[0011]
[0012] Phytic acid contains a large number of phosphate groups and cyclic molecular structures. Compared with simple phosphoric acid and potassium dichromate, it has better chelation and easy adsorption to form a sticky film. It can effectively cooperate with the strong oxidizing dichromic acid and sulfuric acid in the polishing process of the ferrite product surface, improve the polishing efficiency and quality, and reduce the amount of potassium dichromate and sulfuric acid.
[0013] The polyether-modified polysiloxane quaternary ammonium salt may be a water-soluble polysiloxane product containing a hydrophilic polyether chain and a quaternary ammonium salt group commonly used in the market.
[0014] Preferably, the polyether-modified polysiloxane quaternary ammonium salt used in the present invention comprises a molecular structure as described in Formula 2 below:
[0015]
[0016] In the formula, m is an integer of 1-50, n is an integer of 1-50, x is an integer of 1-20, and y is an integer of 0-10.
[0017] In the present invention, the polyether-modified polysiloxane quaternary ammonium salt has good water solubility, low surface tension properties (wetting and spreading) and cationic properties, which can promote the formation of a sticky film of phytic acid molecules and the wetting, penetration and adsorption on the raised burr parts, making the raised burr parts oxidized faster, and using its surface activity to promote the oxide layer to diffuse faster and dissolve in the acid solution, significantly improving the polishing efficiency and quality.
[0018] The polyether-modified polysiloxane quaternary ammonium salt can be prepared by the following method:
[0019] (1) heating hydrogen-containing silicone oil and allyl polyether to 70-90° C. in the absence of solvent or with an organic solvent, adding chloroplatinic acid catalyst to carry out a hydrosilylation reaction to obtain a polyether-modified polysiloxane;
[0020] (2) adding the obtained polyether-modified polysiloxane into water to dissolve evenly, then adding alkaline solution to adjust the pH to 10-14, raising the temperature to 60-80° C., and dropping a cationic etherifying agent solution to carry out an etherification reaction to obtain a polyether-modified polysiloxane quaternary ammonium salt.
[0021] The hydrogen-containing silicone oil preferably has a molecular weight of 500 to 6000 and a hydrogen content of 0.2 to 1 wt%.
[0022] The allyl polyether is preferably allyl polyoxyethylene ether or allyl polyoxyethylene polyoxypropylene ether having a molecular weight of 200 to 800.
[0023] The mass ratio of the hydrogen-containing silicone oil to the allyl polyether is 100:60-150.
[0024] The alkali solution is preferably a sodium hydroxide solution or a potassium hydroxide solution.
[0025] The cationic etherifying agent is preferably 3-chloro-2-hydroxypropyltrimethylammonium chloride or 2,3-epoxypropyltrimethylammonium chloride; the amount of the cationic etherifying agent added is 3% to 12% of the mass of the polyether-modified polysiloxane.
[0026] The preparation method of the polyether modified polysiloxane quaternary ammonium salt has simple and easily available raw materials, a simple and easy to control preparation process, and a low preparation cost.
[0027] The preparation method of the above chemical polishing liquid comprises the following steps:
[0028] Potassium dichromate is added into water and dissolved evenly, then phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride are added in sequence and stirred to dissolve evenly, and finally sulfuric acid is added and mixed to obtain a chemical polishing solution.
[0029] Application of the above chemical polishing liquid in chemical polishing of ferrite products.
[0030] Preferably, the application method is: immersing the ferrite product containing burrs in the above chemical polishing solution and letting it stand for 1 to 15 minutes, taking it out and rinsing it with deionized water and drying it to obtain a polished ferrite product.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention adopts phytic acid to replace phosphoric acid and potassium dichromate in conventional chemical polishing liquid, which has better chelation and easy formation of sticky film with potassium dichromate, and can effectively cooperate with strong oxidizing dichromic acid and sulfuric acid in the polishing process of the surface of ferrite products, improve polishing efficiency and quality, and reduce the amount of potassium dichromate and sulfuric acid.
[0033] (2) Based on the large specific surface area and surface energy of the burr part, the low surface tension and easy wetting and spreading characteristics of the polyether-modified polysiloxane quaternary ammonium salt and its good binding force with phytic acid molecules can promote the formation of a sticky film of phytic acid molecules and the wetting, penetration and adsorption on the raised burr part, thereby significantly improving the polishing efficiency and quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The surface microscopic morphology of the ferrite product in Example 1 before and after chemical polishing.
[0035] Figure 2 This is a detection diagram of the burr surface morphology of the ferrite product in Example 1 before and after chemical polishing. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0037] The polyether-modified polysiloxane quaternary ammonium salt used in the following examples is prepared by the following method:
[0038] (1) By weight, 100 parts of hydrogen-containing silicone oil with an average molecular weight of 3000 and a hydrogen content of 0.55 wt% and 100 parts of allyl polyoxyethylene ether with an average molecular weight of 400 were heated to 80° C. in isopropanol solvent, and chloroplatinic acid isopropanol solution was added as a catalyst to carry out a hydrosilylation reaction for 6 hours to obtain a polyether-modified polysiloxane.
[0039] (2) 100 parts of the obtained polyether-modified polysiloxane are added to water and dissolved evenly, then sodium hydroxide solution is added to adjust the pH to 12, the temperature is raised to 70° C., and an aqueous solution containing 8 parts of a cationic etherifying agent 2,3-epoxypropyltrimethylammonium chloride is added dropwise to carry out an etherification reaction for 6 hours to obtain a polyether-modified polysiloxane quaternary ammonium salt.
[0040] Example 1
[0041] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0042] Sulfuric acid 4%, phytic acid 5%, potassium dichromate 4%, polyether modified polysiloxane quaternary ammonium salt 5%, sodium chloride 2%, deionized water 80%.
[0043] The preparation method of the above chemical polishing liquid comprises the following steps:
[0044] Prepare each component according to the mass percentage, add potassium dichromate into deionized water to dissolve evenly, then add phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride in sequence and stir to dissolve evenly, finally add concentrated sulfuric acid and mix well to obtain a chemical polishing solution.
[0045] The application of the chemical polishing liquid in the chemical polishing of ferrite products. The application method is as follows:
[0046] The ferrite product containing burrs is immersed in the above chemical polishing solution and allowed to stand for 10 minutes. After being taken out, it is rinsed with deionized water and dried to obtain a polished ferrite product.
[0047] The surface microscopic morphology of the ferrite product in this embodiment before and after chemical polishing is as follows Figure 1 shown.
[0048] The burr surface morphology detection diagram of the ferrite product in this embodiment before and after chemical polishing is as follows Figure 2 As shown. Figure 2 The results show that the highest point of the burr before chemical polishing is 118.91um, and the red distribution area is larger; the highest point after chemical polishing is 113.09um, and the red distribution area is significantly reduced.
[0049] The roughness R of the ferrite product in this embodiment is tested before and after chemical polishing. a They are 1.72μm and 0.16μm respectively. The polishing effect is good.
[0050] The above results show that the chemical polishing liquid of the present invention can effectively remove the abnormal burrs on the appearance of ferrite products and significantly reduce the surface roughness of ferrite products, thereby significantly improving the polishing efficiency and quality.
[0051] Example 2
[0052] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0053] Sulfuric acid 6%, phytic acid 3%, potassium dichromate 6%, polyether modified polysiloxane quaternary ammonium salt 4%, sodium chloride 1%, deionized water 80%.
[0054] The preparation method of the above chemical polishing liquid comprises the following steps:
[0055] Prepare each component according to the mass percentage, add potassium dichromate into deionized water to dissolve evenly, then add phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride in sequence and stir to dissolve evenly, finally add concentrated sulfuric acid and mix well to obtain a chemical polishing solution.
[0056] The application of the chemical polishing liquid in the chemical polishing of ferrite products. The application method is as follows:
[0057] The ferrite product containing burrs is immersed in the above chemical polishing solution and allowed to stand for 15 minutes. After being taken out, it is rinsed with deionized water and dried to obtain a polished ferrite product.
[0058] The roughness R of the ferrite product in this embodiment is tested before and after chemical polishing. a They are 1.66μm and 0.15μm respectively. The polishing effect is good.
[0059] Example 3
[0060] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0061] Sulfuric acid 8%, phytic acid 2%, potassium dichromate 1%, polyether modified polysiloxane quaternary ammonium salt 2%, sodium chloride 0.5%, deionized water 86.5%.
[0062] The preparation method of the above chemical polishing liquid comprises the following steps:
[0063] Prepare each component according to the mass percentage, add potassium dichromate into deionized water to dissolve evenly, then add phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride in sequence and stir to dissolve evenly, finally add concentrated sulfuric acid and mix well to obtain a chemical polishing solution.
[0064] The application of the chemical polishing liquid in the chemical polishing of ferrite products. The application method is as follows:
[0065] The ferrite product containing burrs is immersed in the above chemical polishing solution and allowed to stand for 5 minutes. After being taken out, it is rinsed with deionized water and dried to obtain a polished ferrite product.
[0066] The roughness R of the ferrite product in this embodiment is tested before and after chemical polishing. a They are 1.62μm and 0.21μm respectively. The polishing effect is good.
[0067] Example 4
[0068] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0069] Sulfuric acid 5%, phytic acid 4%, potassium dichromate 5%, polyether modified polysiloxane quaternary ammonium salt 1%, sodium chloride 0.2%, deionized water 84.8%.
[0070] The preparation method of the above chemical polishing liquid comprises the following steps:
[0071] Prepare each component according to the mass percentage, add potassium dichromate into deionized water to dissolve evenly, then add phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride in sequence and stir to dissolve evenly, finally add concentrated sulfuric acid and mix well to obtain a chemical polishing solution.
[0072] The application of the chemical polishing liquid in the chemical polishing of ferrite products. The application method is as follows:
[0073] The ferrite product containing burrs is immersed in the above chemical polishing solution and allowed to stand for 15 minutes. After being taken out, it is rinsed with deionized water and dried to obtain a polished ferrite product.
[0074] The roughness R of the ferrite product in this embodiment is tested before and after chemical polishing. a They are 1.51μm and 0.19μm respectively. The polishing effect is good.
[0075] Example 5
[0076] A chemical polishing liquid for ferrite products, comprising the following components in percentage by mass:
[0077] Sulfuric acid 7%, phytic acid 3%, potassium dichromate 3%, polyether modified polysiloxane quaternary ammonium salt 3%, sodium chloride 1%, deionized water 83%.
[0078] The preparation method of the above chemical polishing liquid comprises the following steps:
[0079] Prepare each component according to the mass percentage, add potassium dichromate into deionized water to dissolve evenly, then add phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride in sequence and stir to dissolve evenly, finally add concentrated sulfuric acid and mix well to obtain a chemical polishing solution.
[0080] The application of the chemical polishing liquid in the chemical polishing of ferrite products. The application method is as follows:
[0081] The ferrite product containing burrs is immersed in the above chemical polishing solution and allowed to stand for 10 minutes. After being taken out, it is rinsed with deionized water and dried to obtain a polished ferrite product.
[0082] The roughness R of the ferrite product in this embodiment is tested before and after chemical polishing. a They are 1.54μm and 0.17μm respectively. The polishing effect is good.
[0083] Comparative Example 1
[0084] A chemical polishing liquid, compared with Example 1, uses an equal amount of phosphoric acid to replace phytic acid, and the rest is the same.
[0085] The roughness R of the ferrite product in this comparative example before and after chemical polishing was tested. a They are 1.60 μm and 0.47 μm respectively.
[0086] It can be seen from the above results that the phytic acid used in the present invention can effectively cooperate with the strong oxidizing dichromic acid and sulfuric acid in the polishing process on the surface of the ferrite product, thereby improving the polishing effect, compared with conventional phosphoric acid.
[0087] Comparative Example 2
[0088] A chemical polishing liquid, compared with Example 1, uses an equal amount of phosphoric acid to replace phytic acid, and increases the concentration of sulfuric acid to 10%, and the concentration of potassium dichromate to 6%. The chemical polishing liquid specifically comprises the following components in percentage by weight:
[0089] Sulfuric acid 10%, phosphoric acid 5%, potassium dichromate 6%, polyether modified polysiloxane quaternary ammonium salt 5%, sodium chloride 2%, deionized water 72%.
[0090] The roughness R of the ferrite product in this comparative example before and after chemical polishing was tested. a They are 1.68μm and 0.26μm respectively.
[0091] It can be seen from the above results that the phytic acid used in the present invention can effectively cooperate with the strong oxidizing dichromic acid and sulfuric acid in the polishing process of the ferrite product surface compared with conventional phosphoric acid, and can achieve better polishing effect under the condition of lower potassium dichromate and sulfuric acid dosage.
[0092] Comparative Example 3
[0093] A chemical polishing liquid, compared with Example 1, does not add polyether-modified polysiloxane quaternary ammonium salt. The chemical polishing liquid specifically comprises the following components in percentage by weight:
[0094] Sulfuric acid 4%, phytic acid 5%, potassium dichromate 4%, sodium chloride 2%, deionized water 85%.
[0095] The roughness R of the ferrite product in this comparative example before and after chemical polishing was tested. a They are 1.73 μm and 0.54 μm respectively.
[0096] It can be seen from the above results that the use of polyether-modified polysiloxane quaternary ammonium salt in the present invention can promote the formation of phytic acid molecular adhesive film and the wetting, penetration and adsorption on the raised burr part, thereby significantly improving the polishing effect.
[0097] Comparative Example 4
[0098] A chemical polishing liquid, compared with Example 1, uses an equal amount of conventional cationic surfactant hexadecyltrimethylammonium chloride to replace the polyether modified polysiloxane quaternary ammonium salt, and the rest is the same.
[0099] The roughness R of the ferrite product in this comparative example before and after chemical polishing was tested. a They are 1.69μm and 0.41μm respectively.
[0100] It can be seen from the above results that the polyether-modified polysiloxane quaternary ammonium salt used in the present invention has a polysiloxane main chain with better wetting and spreading properties than conventional cationic surfactants, can better promote the formation of phytic acid molecular sticky film and the wetting, penetration and adsorption on the raised burr part, and significantly improve the polishing effect.
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A chemical polishing liquid for ferrite products, characterized in that: Contains the following ingredients in percentage by mass: Sulfuric acid 4%~8%, phytic acid 2%~5%, potassium dichromate 1%~6%, polyether modified polysiloxane quaternary ammonium salt 0.5%~5%, sodium chloride 0.2%~2%, and the rest is water; The polyether-modified polysiloxane quaternary ammonium salt has a molecular structure as described in Formula 2: Formula 2, Wherein m is an integer of 1 to 50, n is an integer of 1 to 50, x is an integer of 1 to 20, and y is an integer of 0 to 10; The polyether-modified polysiloxane quaternary ammonium salt is prepared by the following method: (1) heating the hydrogen-containing silicone oil and allyl polyether to 70-90°C in the absence of solvent or in an organic solvent, adding chloroplatinic acid catalyst to carry out a hydrosilylation reaction to obtain a polyether-modified polysiloxane; (2) adding the obtained polyether-modified polysiloxane into water to dissolve evenly, then adding alkaline solution to adjust the pH to 10-14, raising the temperature to 60-80° C., and dropping a cationic etherifying agent solution to carry out an etherification reaction to obtain a polyether-modified polysiloxane quaternary ammonium salt; The hydrogen-containing silicone oil is a hydrogen-containing silicone oil with a molecular weight of 500-6000 and a hydrogen content of 0.2-1wt%; the allyl polyether is an allyl polyoxyethylene ether or an allyl polyoxyethylene polyoxypropylene ether with a molecular weight of 200-800; The mass ratio of the hydrogen-containing silicone oil to the allyl polyether added is 100:60-150; The cationic etherifying agent is 3-chloro-2-hydroxypropyltrimethylammonium chloride or 2,3-epoxypropyltrimethylammonium chloride; the amount of the cationic etherifying agent added is 3% to 12% of the mass of the polyether-modified polysiloxane.
2. The chemical polishing liquid for ferrite products according to claim 1, characterized in that: The alkali solution is a sodium hydroxide solution or a potassium hydroxide solution.
3. The method for preparing a chemical polishing solution according to claim 1 or 2, characterized in that: The steps include: Potassium dichromate is added into water and dissolved evenly, then phytic acid, polyether modified polysiloxane quaternary ammonium salt and sodium chloride are added in sequence and stirred to dissolve evenly, and finally sulfuric acid is added and mixed to obtain a chemical polishing solution.
4. Use of a chemical polishing liquid as claimed in claim 1 or 2 in chemical polishing of ferrite products.
5. The use according to claim 4, characterized in that: The application method comprises: immersing the ferrite product containing burrs in the chemical polishing liquid of claim 1 or 2 and letting it stand for 1 to 15 minutes, taking it out and rinsing it with deionized water, and drying it to obtain a polished ferrite product.
Citation Information
Patent Citations
Chemical mechanical polishing liquid
CN102093816A
Chemical polishing solution for environment-friendly copper product and preparation method of chemical polishing solution
CN103409757A